1990
DOI: 10.1111/j.1365-2621.1990.tb01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of controlled atmospheres on microbial spoilage, electrolyte leakage and sugar content of fresh ‘ready‐to‐use’ grated carrots

Abstract: The effects of controlled atmospheres (C02 concentrations ranging from 0.03 to 40% and 0 2 concentrations ranging from 21 to lob, measured in pack) were studied on fresh 'ready-to-use' grated carrots, stored at 10°C. High C02 or low 0 2 conditions favour the growth of lactic acid bacteria (LAB) on grated carrots, but not in a sterile carrot medium, and induce an increased potassium ion leakage. A 25% COz and 2% O2 atmosphere improves retention of sugars. Grated carrots were inoculated by a strain of Leuconosto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
8

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 10 publications
1
26
0
8
Order By: Relevance
“…BENEDETTI et al [4] found a decrease from 0.08 to 0.06 mg 100 g of citric acid in sliced green peppers packed in polystyrene trays and stored for 10 days under temperatures of 5 and 10ºC and CARLIN et al [8] reported a decrease in malic acid in grated carrots packed under modified atmosphere (10% O 2 and 40% CO 2 ) for 10 days at 10ºC.…”
Section: -Titratable Aciditymentioning
confidence: 99%
See 1 more Smart Citation
“…BENEDETTI et al [4] found a decrease from 0.08 to 0.06 mg 100 g of citric acid in sliced green peppers packed in polystyrene trays and stored for 10 days under temperatures of 5 and 10ºC and CARLIN et al [8] reported a decrease in malic acid in grated carrots packed under modified atmosphere (10% O 2 and 40% CO 2 ) for 10 days at 10ºC.…”
Section: -Titratable Aciditymentioning
confidence: 99%
“…Reviews by ZAGORY & KADER [46]; CARLIN et al [8]; IZUMI et al [19]; GIL et al [16] and JAYAS & JEYAMKONDAN [21] show the relevance of the use of O 2 , CO 2 and N 2 modified atmosphere in the storage of minimally processed vegetables.…”
mentioning
confidence: 99%
“…The model that best fitted the experimental data, however, were those obtained at 1 °C. Carlin et al (1990) stated that low density polypropylene and polyethylene films generally resulted in considerable modifications of the atmosphere inside the package when used to store processed carrots reaching levels above 30% for CO 2 and below 5% for O 2 . However, in the present study, although considerable modifications in the internal atmosphere were observed, such extremely high values for the CO 2 concentration were not obtained.…”
Section: Determination Of the Gas Compositionmentioning
confidence: 99%
“…The level of sugars is important not only by its nutritional value but also by the physiological role that sugars have on senescence. Several reports have shown that treatments that delay the sugar loss (Carlin et al 1990, Costa et al2005, Lemoine et al 2007 or treatments that feed with glucose or sucrose (Nishikawa et al 2005, Hasperué et al 2011 can delay postharvest senescence.…”
Section: Introductionmentioning
confidence: 99%